Synthesis and Characterization of Bentonite/Graphene/Chitosan Nanocomposites - Permana, Edwin; Damris, Muhammad; Lestari, Intan; Marlinda, Lenny; B., Muh. Rizal; Fadli, Riskal; Hidayat, Ali Nurdin (Proceeding International Conference on Religion, Science and Education, 2026)
Bentonite has been widely utilized as a natural adsorbent; however, it exhibits relatively low effectiveness and selectivity, necessitating its combination with other supporting materials. Graphene and chitosan possess strong capabilities for binding metal ions in water due to their high surface area. Therefore, integrating bentonite with graphene and chitosan can produce an adsorbent with enhanced selectivity. This study aims to develop and optimize a bentonite–graphene–chitosan–based nanocomposite adsorbent for removing Fe3+ ions from contaminated water. The nanocomposite was prepared through the synthesis of graphene oxide, activation of bentonite, and incorporation of chitosan, followed by characterization using XRD and FTIR. The FTIR and XRD results indicate that each component retains its characteristic features, and graphene oxide is successfully formed in an amorphous structure. The combination of these three materials shows strong potential as an Fe3+ adsorbent due to the synergistic interaction among the cation-exchange capacity of bentonite, the active surface of graphene oxide, and the amino functional groups of chitosan.